The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/coatings10040304
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Targeting Delivery of Terbinafine Hydrochloride Using Novel Multi-Ethosomes: A New Approach to Fungal Infection Treatment

Abstract: This research aimed to develop and evaluate a novel multi-ethosome (ME) system for the dermal delivery of terbinafine hydrochloride (TH) as a new approach to fungal infection treatment. TH-loaded MEs were successfully prepared using cinnamaldehyde as a penetration enhancer. Mean diameter of ME was found as ~100 nm with monodispersed size distribution. Drug entrapment efficiency reached up to 86% ± 1.4%. MEs exhibited excellent colloid stability and no drug leakage after 2 months of storage. In contrast to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…As reported by Zhang et al. while targeting dermal fungus infection using vesicle nanocarrier loaded with terbinafine hydrochloride, a maximizing in ZP contributed to higher repulsive forces that enhanced vesicle stability and improved the interaction with the skin layers, which is in agreement with current findings (L. Zhang et al., 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…As reported by Zhang et al. while targeting dermal fungus infection using vesicle nanocarrier loaded with terbinafine hydrochloride, a maximizing in ZP contributed to higher repulsive forces that enhanced vesicle stability and improved the interaction with the skin layers, which is in agreement with current findings (L. Zhang et al., 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…It was found that ME significantly improved the targeting efficiency as compared commercial Lamisil ® cream. The improved antifungal activity of ME confirmed by in vitro minimum inhibitory concentration (MIC) assay on Candida albicans strains [55].…”
Section: Application Of Ethosomal Formulations In Fungal Therapeuticsmentioning
confidence: 92%
“…The microdilution method determined the minimum inhibitory concentration (MIC) values of evaluated samples against C.albicans and A.fumigatus ( Zhang et al, 2020 ). The assay was performed on the free ATO, blank EML-foam, and ATO-EMLs foam system.…”
Section: Methodsmentioning
confidence: 99%